A combined approach for a modern hydrogeological mapping: the case study of Tennacola stream catchment (central Apennine, Italy). Issue 2 (3rd July 2019) - Giacopetti, Marco; Materazzi, Marco; Pambianchi, Gilberto; Posavec, Kristijan
ABSTRACT: The current European water legislation, specifically the one addressed to groundwater for human consumption (EU Water Framework Directive, WFD-2000/60/EC), provides clear indications on the objectives and actions to be taken for the proper management and protection of water resources. In Italy, as well as in other countries of the EU, the implementation of this Directive, in the face of an adjustment of the legislation at national level, is still far behind, as regards the obligations on the part of local administrations. Among the reasons there is a lack of cognitive tools, adequate and, above all, univocally accepted by the scientific point of view. The hydrogeological mapping here presented, which covers an area of around 44 km 2 and is edited at 1:10, 000 scale, goes in this direction, combining different approaches and methodologies (field surveys, spring hydrograph analysis, surface flow measurements, numerical models …) to arrive at a complete and functional study of an aquifer exploited for drinking purposes.